The Effect of Different File Motions on the Formation of Apical Debris During Root Canal Preparation In vitro - Athul B. Kurian; Tansha; Rubal Singh; Raman Mishra; Ashtha Arya; Smitha Reddy (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: After root canal preparation, apical debris may cause discomfort and delayed healing. Rotary, reciprocating, and adaptive file movements affect debris extrusion. Materials and Methods: Sixty extracted mandibular premolars with single root canals were randomly divided into three file motion groups (n = 20): Group A (rotary motion using ProTaper Universal files), Group B (reciprocating motion using WaveOne files), and Group C (adaptive motion using TF Adaptive files). Extruded debris was collected in Eppendorf tubes with teeth. Standard watering techniques prepared root canals. Drying and weighing extruded debris with a 0.0001 g analytical balance detected apical debris. Results: The average weight of extruded debris in Group A (rotary) was 0.120 ± 0.005 g, Group B (reciprocating) was 0.180 ± 0.008 g, and Group C (adaptive motion) was 0.140 ± 0.006 g. One-way ANOVA analysis showed significant differences across groups (P < 0.05). The rotating motion extruded the least apical debris, whereas reciprocating action generated the most. Conclusion: File movements greatly affect apical debris production during root canal preparation. Apical debris is lowest with rotary motion, followed by adaptive and reciprocating motion.